DIAGNOSIS AND TREATMENT OF VARICEAL BLEEDING - Popovic, Dusan; Marjanovic Haljilji, Marija; Mijac, Dragana; Martinov-Nestorov, Jelena; Trbojevic-Stankovic, Jasna; Radojkovic, Milica; Filipovic, Branka (Medical Research, 2026)
Portal hypertension is defined as an increase in the hepatic venous pressure gradient, most commonly resulting from liver cirrhosis and leading to the development of portosystemic collaterals, particularly esophageal varices. At the time of cirrhosis diagnosis, approximately 50% of patients have esophageal varices, and variceal bleeding represents one of the most severe and life-threatening complications in gastroenterology. Esophagogastroduodenoscopy is the cornerstone for both diagnosis and treatment of acute variceal bleeding. Therapeutic options include endoscopic hemostasis, pharmacological therapy, balloon tamponade, interventional radiology procedures, and surgical interventions. Endoscopic band ligation is the preferred first-line endoscopic treatment, while sclerotherapy, involving intravariceal or paravariceal injection of sclerosant agents, is now used less frequently. Pharmacological management includes splanchnic vasoconstrictors such as octreotide, terlipressin, vapreotide, and somatostatin analogues, along with supportive measures including fluid resuscitation, blood product transfusion, and correction of coagulopathy. Prophylactic antibiotic therapy, most commonly with fluoroquinolones or cephalosporins, is mandatory in cirrhotic patients with variceal bleeding. Balloon tamponade using devices such as Sengstaken–Blakemore, Minnesota, or Linton–Nachlas tubes serves as a temporary rescue therapy. In cases refractory to standard treatment, transjugular intrahepatic portosystemic shunt (TIPS) or surgical management may be considered in carefully selected patients. Management of variceal bleeding requires intensive care and a multidisciplinary approach.